A rural-urban comparison of ownership and utilization of Long-Lasting Insecticide Treated Nets among pregnant women in Ogun State Nigeria - Temitope Ladi-Akinyemi; Babatunde Ladi-Akinyemi; Adedoyin Ogunyemi; Francis Oluwole (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2019)
Background: The use of Long-Lasting Insecticide Treated Nets (LLINs) in Africa increased mean birth weight by 55g, reduced the incidence of low birth weight by 23% and decreased miscarriages/stillbirths by 33%. However, the benefit of the LLINs may be limited by the rate of ownership and utilization by pregnant women. Objective: To determine and compare the ownership and utilization of LLINs among pregnant women in urban and rural areas of Ogun State. Methods: A community-based comparative cross-sectional study on 72 and 74 pregnant women living in urban and rural areas, respectively of Ogun State was carried out. Using a multi-stage cluster sampling technique and a pretested semi-structured interviewer-administered questionnaire, information on LLINs ownership and use were obtained. Results: Ownership of LLINs was 81.1% in rural areas compared to 66.7% in urban areas. About 65% of participants in rural versus 44.4% in urban areas slept under LLINs. The predictor of ownership of LLIN was age group 15-24 years [AOR 0.10 (95%CI 0.01 - 0.56)]. The predictors of utilization of LLINs included urban residence [AOR 0.29 (95%CI 0.13 - 0.65)], age group 15-24 years [AOR 0.17 (95%CI 0.04 - 0.70)], registration of pregnancy for antenatal care [AOR 5.12 (95%CI 1.14 - 23.03)] and knowledge on prevention of malaria [AOR 4.94 (95%CI 1.51 - 16.17)]. Conclusion: Pregnant women should visit ANC clinics regularly, and health education on malaria should focus more on the prevention of malaria as well as encouraging the consistent use of the nets, particularly in the urban areas.